Characteristics and Possibilities of Software Tool for Metal-Oxide Surge Arresters Selection - Đorđević, Dragan; Stojković, Zlatan; Ivanov, Aleksandar (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
This paper presents a procedure for the selection of metal-oxide surge arresters based on the instructions given in the Siemens and ABB catalogues, respecting their differences and the characteristics and possibilities of the software tool. The software tool was developed during the preparation of a Master’s thesis titled, "Automation of Metal-Oxide Surge Arresters Selection". An example is presented of the selection of metal-oxide surge arresters using the developed software tool.